The Role of the Judiciary in the Enforcement of Arbitral Awards in Jordan - Alrawashdeh, Waddah (Pécs journal of international and European law, 2017)
This paper discusses the main role of the judiciary in the enforcement of arbitral awards in Jordan depends on the Law governing the enforcement of the arbitration under Jordanian Arbitration Law No. 31 for the year 2001 and Jordanian Law for the Implementation of Foreign Judgments No. 8 for the year 1952.